Interstate protectionism: the case of solar renewable energy credits. Issue 2 (29th July 2021) - Cohen, Jed J.; Elbakidze, Levan; Jackson, Randall
Abstract: Solar Renewable Energy Credits (SRECs) are financial instruments created by state policies to offer incentives for generating solar energy. In an effort to support in‐state solar energy sectors and boost local employment opportunities, some states have closed off their SREC markets to out‐of‐state solar facilities. We examine the merits of such protectionist policy from the protectionist state's perspective. We find that SREC market closure leads to higher in‐state SREC prices and greater solar installation, and is associated with lower electricity prices. The study illustrates the economic incentives for protecting in‐state SREC markets from out‐of‐state solar energy producers.